Analysis of the complete mitochondrial genomes of two forensically important blowfly species: Lucilia caesar and Lucilia illustris. Issue 2 (3rd July 2018) - Schoofs, Kathleen R.; Krzeminska Ahmadzai, Urszula; Goodwin, William
Abstract: Blowfly species of the family Calliphoridae can be used in forensic investigations to estimate the minimum post-mortem interval (PMImin ). Lucilia caesar and Lucilia illustris (Diptera: Calliphoridae) are closely related and phenotypically similar, making reliable identification difficult. To identify potential genetic markers to distinguish these species, five complete mitochondrial genomes were sequenced: three for L. caesar (KM657111–KM657113) and two for L. illustris (KM657109, KM657110). The ND6 gene contained the most species-specific SNPs (1.71%), followed by the ND5 gene (1.68%) and the COI gene (1.56%), identifying ND6 and ND5 as valuable loci for differentiating L. caesar and L. illustris specimens.